"A Good Wife Brings Her Husband Bath Water": Gender Roles and Water Practices in Nampula, Mozambique. Issue 9 (1st September 2016) - Van Houweling, Emily
ABSTRACT: In the Global South, gender roles and relations are closely connected to water collection and use. The aim of this article is to move beyond the simple development associations linking improved water access with women's empowerment by showing how gender roles, marital relations, and the division of labor are connected to everyday water practices. Ethnographic research took place in five communities in Nampula, Mozambique, during a year when residents endured seasonal dry months and later received a water supply project. This research explores how gender roles and relations are impacted by changes in community water resources, and how these impacts are understood from local perspectives. In rural Mozambique, water collection and use are not only gendered activities, but also practices that shape marital relations and cultural notions of a good wife and mother.